2006
DOI: 10.1139/e05-097
|View full text |Cite
|
Sign up to set email alerts
|

Late Permian (Changhsingian) conodont biozonation and the basal boundary, Ganxi section, western Hubei Province, south China

Abstract: Four neogondolellid conodont interval zones were recognized across the Changhsingian stage at Ganxi section, western Hubei Province, south China. They are in ascending order: the Clarkina wangi Zone, the Clarkina changxingensis changxingensis Zone, the Clarkina changxingensis yini Zone, and the Clarkina meishanensis meishanensis Zone. The present study suggests that the base of the Changhsingian can be defined by the first appearance datum (FAD) of Clarkina wangi within an evolutionary lineage from Clarkina lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…The C. wangi Zone was also confirmed by Shen and Mei (2010) from sections in Iran, but again without any illustrations of the materials. In their paper (and in Nafi et al, 2006;Chen et al, 2008) C. hambastensis was regarded as a probable synonym of C. wangi. Shen and Mei (2010) indicated that C. hambastensis is less common in the population of C. wangi in South China.…”
Section: Conodont Stratigraphy (Ghaderi Ashouri)mentioning
confidence: 98%
“…The C. wangi Zone was also confirmed by Shen and Mei (2010) from sections in Iran, but again without any illustrations of the materials. In their paper (and in Nafi et al, 2006;Chen et al, 2008) C. hambastensis was regarded as a probable synonym of C. wangi. Shen and Mei (2010) indicated that C. hambastensis is less common in the population of C. wangi in South China.…”
Section: Conodont Stratigraphy (Ghaderi Ashouri)mentioning
confidence: 98%
“…1, figures 1-6 Diagnosis: See detailed diagnosis of Mei et al (2004). Clarkina hambastensis was regarded as a form of C. wangi with a posterior pointed protrusion and wall-like, highly fused posterior denticles by Nafi et al (2006) and by Chen et al (2008). Our study indicates that this form probably represents a small amount of specimens that are less common in the population of C. wangi in South China.…”
Section: -----------------------------------------mentioning
confidence: 99%
“…4. The lithostratigraphic correlation between the nearby Ganxi section (Nafi et al, 2006) capillary column used was 60 m  0.25 mm in size, with 0.25 lm film. The sample was injected with an injector temperature of 300°C.…”
Section: Methodsmentioning
confidence: 99%
“…Paleogeographically, the Ganxi section was probably deposited in deeper water than the Zhaojiaba. Nafi et al (2006) had analyzed the conodonts at Ganxi in detail to constrain the W-C boundary in the Lopingian and the P-Tr boundary. Lithologically, the upper Wuchiapingian and the entire Changhsingian in the Ganxi section mainly consists of mudstones interrupted by two limestone intervals, one is in lower Changhsingian and the other in the upper Changhsingian (Fig.…”
Section: Age Constraints By Stratigraphic Correlationsmentioning
confidence: 99%
See 1 more Smart Citation